THREAT FROM WARRING PARTIES: A CHALLENGE FOR LOCAL JOURNALISTS OF DISTRICT SWAT COVERING INTERNAL CONFLICT - Rafi Ullah; Dr. Mahboob Ali; Khayam Hassan; Dr. Jamal Ud Din (International Journal of Contemporary Issues in Social Sciences, 2023)
This research investigates the challenges and threats local journalists faced during the militant conflict in the Swat district of Pakistan. Through interviews with journalists in the region, the study explores how they navigate the complexities of reporting traumatic events, and threats while grappling with physical and emotional stress. Employing Pierre Bourdieu’s Field Theory, the research analyzes journalists’ strategies to counter threats from warring parties remain safe in the conflict zones, and ensure the journalistic principles. Using concepts like Habitus, and Doxa, the study situates journalists within the volatile social landscape to highlight the relationship of their professional and personal spheres. Despite possessing cultural and social capital, journalists face significant risks to their safety while fulfilling their reporting duties in dangerous environments.